Management of Change System with Integrated Risk Analysis for Temporary and Emergency Cases - Pang, Kar Kei; Hanida, Abdul Aziz (Universiti Putra Malaysia, 2020)
The Potential of a major accident may significantly increase when change is unprepared especially in a temporary and emergency change. An unplanned change may lead to the emergence of new hazards which eventually lead towards severe impact on human, property, environment and business reputation. Management of Change (MOC) with integrated risk analysis is an important Process Safety Management (PSM) elements involving planning and controlling risks and hazards that come with the proposed change. However, lacking systematic technique for easy adoption of this element has delayed its application in plant. Corresponding to these weaknesses, an integrated MOC management system focusing on the temporary and emergency change is presented in this study. Results of this study comprise MOC process framework and MOC management system (MOCMS) which act as a guidance and documentation inventory tool. Implementation of this technique and system at the selected plant as a case study is examined and discussed. The system is beneficial to industries to manage underlying risks in a temporary and emergency change which ease the tracking of MOC case inventory to improve risk controls in changes.